First afebrile seizures: Clinical and radiological view with emergent testing - YAPICI, ÖZGE (My University, 2022)
Background The first afebrile seizures in children are an important and common reason for emergency department admissions. We aim to examine the presentation, laboratory/neurodiagnostic investigation, and emergency management of children with first afebrile seizures. Methods The retrospective study included 333 patients aged 1 month to 18 years admitted with a first afebrile seizure to the pediatric emergency department of Prof. Dr. Cemil Tascioglu City Hospital between January 2017 and January 2020. Age, gender, seizure duration and type, treatments for seizures, laboratory, neurophysiological, and radiological investigations, ward or intensive care unit hospitalizations, and antiepileptic drugs on discharge were recorded. Results The average age of the patients was 81.6 +/- 62.9 months; 187 (56.2%) were male and 146 (43.8%) were female. Two hundred and sixty-one (78.4%) patients had only one seizure. In 45 (13.5%) of the patients, the seizure recurred in the emergency department. Hypoglycemia, hyponatremia, and hypocalcemia were detected in 13 (3.9%) patients. Patients with clinically significant cranial computed tomography results were at an increased risk for seizures lasting longer than 5 min. Patients with focal seizures had more recurrences, were given more antiepileptic drugs during the emergency, had better known etiology, more intensive care unit hospitalization, and greater post-discharge antiepileptic drug prescription. Conclusions Biochemical abnormalities remain in the background in the etiology of afebrile seizures. Patients with abnormal neuroimaging on cranial tomography tended to have longer seizures. Patients with focal seizures followed a more complicated course as they had more recurrences and more hospitalization in the intensive care unit.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; child; cranial computed tomography; first afebrile seizure; intensive care unit; status epilepticus; BRAIN COMPUTED-TOMOGRAPHY; NEW-ONSET; RISK-FACTORS; STATUS EPILEPTICUS; AMERICAN ACADEMY; CHILDREN; ABNORMALITIES; SUBCOMMITTEE; INFANTS